Kontribusi Bank Syariah dalam Pemberdayaan Ekonomi Berbasis Zakat, Infak, dan Sedekah (ZIS). - Toyiburahman; Maryani; Ulpariyeh (FEBI UIN Sunan Kalijaga, 2025)
This study aims to analyze the contribution of Islamic banks in empowering the economy based on zakat, infaq, and sadaqah (ZIS) through the collection, management, and productive use of funds. The method used is descriptive qualitative with a literature study approach, covering scientific journals, BAZNAS reports, and the Annual Report of Bank Syariah Indonesia (BSI). The results show that Islamic banks made a significant contribution by increasing ZIS fund collection in 2024, distributing Rp 286.62 million in productive zakat, and implementing empowerment programs such as providing micro-business capital, business assistance, and capacity building training involving BAZNAS, BCA Syariah, and micropreneur mustahik. These programs have an impact on improving the competence, income, and economic independence of mustahik. This study concludes that the contribution of Islamic banks is not only financial but also transformative through capacity building and business sustainability, thereby improving the economic welfare of the community in a sustainable manner.